SEQUENCE BIOSTRATIGRAPHY OF KUNJANG RIVER SECTION, KUTAI BASIN, SAMARINDA, EAST KALIMANTAN - PERDANA PUTRA, ANDRI
Kutai Basin is one of the sedimentary basin that is economically most important in Indonesia. It covers an area of approximately 60,000 km2 and contains Tertiary sediments up to 14 km at the most thick. This basin is the largest and is the deepest Tertiary basin in western Indonesia. Proven petroleum reserves to date is more than 11 billion barrels, making this basin a hydrocarbon field that is really significant on a world scale and petroleum systems of the most productive in the four areas of Southeast Asia - Australia. Additionally this basin contains fairly large coal reserves. Field activities undertaken by performing a brief observation on Kunjang river section and rock sampling in a specific patern and/or systematic intervals. Observations mainly focused on the observation of rock layers sequence, relationship between rock layers, physical properties of rocks and sedimentological aspects that reflect the characteristic facies. From field activities obtained stratigraphic cross-section continuous outcrop of about 400 m thick and 120 samples of sedimentary rocks. Afterward, data analysis has been conducted such as the analysis of facies and facies associations, biozonation determination, and analysis on the depositional environment based on benthic foraminifera associations to do sequence stratigraphy study which guided by sequence biostratigraphy approach. Usefulness of foraminifera fossils in sequence biostratigraphy study of Kunjang river stratigraphic section are very good for biozonation determination and determination of maximum flooding surfaces (MFS), but less complete in determining the depositional environments because of the dilution caused by the high level of acidity in the bottom of the basin and the high rate of sedimentation. Applications of foraminifera fossil in sequence biostratigraphy used as controls in sequence stratigraphy to produce a high-resolution sequence stratigraphic model.